Measuring the Size‐Independent Fracture Energy of Concrete. (22nd November 2012) - Cifuentes, H.; Alcalde, M.; Medina, F.
<x xml:space="preserve">Abstract</x> Abstract: The fracture energy of concrete is an important parameter in the analysis of the mechanical behaviour of concrete structures, so it is considered as a material property. However, the most universal test method for measuring the specific fracture energy of concrete (RILEM work‐of‐fracture) has been a subject of intense debate among researchers. The values have been found to vary with the size and shape of the test specimen. In this study, an experimental comparative analysis of the size‐independent fracture energy obtained by two main methods has been carried out. One of these is based on the local fracture energy model of Hu et al. The second is based on the curtailment of the tail of the P–δ curve by Elices et al. Therefore, the relationship between both methods is highlighted. It is shown that both methods give almost identical results.